2015
DOI: 10.1039/c5cp02268a
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electrochemical microscopy of Li-ion batteries

Abstract: Li-ion batteries (LIBs) are receiving increasing attention over the past decade due to their high energy density. This energy storage technology is expected to continue improving the performance, especially for its large-scale deployment in plug-in hybrid electric vehicles (PHEVs) and full electric vehicles (EVs). Such improvement requires having a large variety of analytical techniques at scientists' disposal in order to understand and address the multiple mechanisms and processes occurring simultaneously in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 76 publications
0
80
0
3
Order By: Relevance
“…to the conductivity enhancing materials. Despite intensive attempts to apply the concepts of SECM to battery materials [63], the direct in-situ imaging of ion intercalation reactions is highly desirable. Previous attempts included the imaging of Li + fluxes by the redox competition mode of SECM using an Hg/Pt micro and nanoelectrodes [64].…”
Section: Application To Ion Intercalation/deintercalation Reactionsmentioning
confidence: 99%
“…to the conductivity enhancing materials. Despite intensive attempts to apply the concepts of SECM to battery materials [63], the direct in-situ imaging of ion intercalation reactions is highly desirable. Previous attempts included the imaging of Li + fluxes by the redox competition mode of SECM using an Hg/Pt micro and nanoelectrodes [64].…”
Section: Application To Ion Intercalation/deintercalation Reactionsmentioning
confidence: 99%
“…For example, miniaturization of active electrode materials scaled down under micrometer scale, discovery of new materials, or development of lithium‐ion (Li + ) based rechargeable systems . As an alternative approach, it is also important to analyze the local electrochemical properties of the electrode materials by probing ion transport or related physical phenomena under in ‐ situ condition at sub‐micrometer scale . Recently, we have shown that a scanning electrochemical cell microscopy with a single barrel nano‐pipette (SECCM) can visualize local Li + redox activities of electrode materials on the surface of the composite practical electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…The SEI formation on model electrodes was also studied using its effect on the Li + intercalation/deintercalation reaction by means of scanning ion‐conductance microscopy . A more comprehensive account of this approach as well as other electrochemical probe techniques is given in another contribution to this Special Issue and other reviews …”
Section: Introductionmentioning
confidence: 99%